Comparative genome wide analysis of the EF-hand containing calcium binding proteins in five edible mushrooms - Nath, Manoj; Mainkar, Pawan; Kansal, Rekha; Bisht, Deepak Singh; Kamal, Shwet; Sharma, Ved Parkash (Mushroom Research, 2024)
The current scenario required urgent attention for the nutritional security and environmental deterioration due to the agricultural wastes. Beneficial fungi are well known for the nutrient recycling, plant growth, soil health and degradation of the plant wastes. Notably, mushrooms, an edible fungus, are an excellent source of the proteins (essential amino acids); vitamins, medicinal properties and can be utilized as food and tonic. Though, several mushroom genomes sequenced in last decade, but the knowledge of the mushroom developmental biology is still meagre. Moreover, calcium is ubiquitous signaling agent in all the eukaryotes, which binds with different calcium binding proteins. The present study reports the genome wide comparative analysis of the EF-hand containing calcium binding proteins of five edible mushrooms viz. Agaricus bisporous var. bisporous H97and Agaricus bisporous var. burnettii JB137-S8; Pleurotus ostreatus strain PC15 ; Lentinula edodes strain NBRC 111202 ; Schizophyllum commune strain H4-8; Coprinopsis cinerea strain okayama7#130. The results demonstrated that EF-hand number ranges from two to five, while EF-hand containing proteins ranges from fourteen to seventeen in all the analysed mushroom genomes. Phylogenetic analysis showed that, EF-hand containing proteins fall into four groups. In general, Group I contain all the CaM and CMLs while Group II includes the CBL and NCS. Group III having all the PEF proteins and Group IV contains remaining proteins in which other functional domain was also present. The comparative information generated in this study could be helpful for functional characterization of the genes of five edible mushrooms and their relationship with important agronomic traits.